Indoor propagation using a game engine ray-based model in indoor scenario at 5.4GHz (2016)
The results of a simulation of signal propagation strength in indoor environment using a game engine ray-based tool and use of an open source 3D modeling tool for scenario building are presented in this paper, showing the flexibility of the XML description language for this kind of scenario. We show simulation results and compare them with an extensive set of measurements for an indoor scenario with multiple materials in the 5.4GHz band, obtaining a good match between the raybased tool and measurements of received power. We found also that constitutive parameters have an important effect on the simulation results and made some small adjustments to improve results.